Peacemaking in an authoritaraian context in Africa: Promoting peace from below in Cameroon - (:unkn) unknown (My University, 2024)
Cameroon, traditionally overlooked on the international peace agenda, has recently received increased attention due to mounting security challenges. Operating under an authoritarian regime that denies conflicts while promoting a narrative of stability, the course of international peace-from-below initiatives is profoundly influenced by this constrained political environment. Through in-depth case studies of three ongoing humanitarian crises—the Central African refugees’ influx, the Boko Haram/Islamic State West Africa Province insurgency, and the Anglophone conflict—this article contends that localized peace approaches, centring on grassroots reconciliation, may obscure broader structural issues, silence non-state political claims from below, and absolve the state of its responsibilities. Embracing such methodologies not only reinforces authoritarian dynamics but also exhibits a performative dimension, contributing to the establishment of a ‘victor’s peace’ in the absence of military victory.
Keywords: African Research